Lexicons on Bamboo Woven in Tigawasa Village: Ecolinguistic Perspective - Ni Ketut Veri Kusumaningrum; I Made Suastra; I Wayan Pastika (e-Journal of Linguistics, 2025)
This study describes the lexicon on woven bamboo in Tigawasa Village, Buleleng in an ecolinguistic perspective. The purpose of this study is to classify the lexicon on woven bamboo in Tigawasa Village and describe the existence of the lexicon. The method used to examine this research is qualitative with ecolinguistic theory. The results of the study found that there was a decrease in the level of knowledge of some people, especially the younger generation about the woven bamboo lexicon in Tigawasa Village. The percentage of the presence of this lexicon is higher indicated by seniors. This is due to 1) changes in the environment and economic activities 2) the process of transmitting the lexicon from the elderly or parents is still lacking due to the influence of the times 3) The use of Balinese and Indonesian languages.